The Urgency of Good Faith Principle Implementation in Indonesian Bankruptcy Regime - Robert, Robert; Sirait, Ningrum Natasya (Universitas Medan Area, 2023)
This article aims to argues the urgency of good faith principle implementation in the Indonesian bankruptcy regime. The problem is focused on describing several flaws in the Indonesian bankruptcy law related to the good faith principle, several example bankruptcy abuse cases in Indonesia. Furthermore, this study also aims to propose notions to minimalize Indonesian bankruptcy regime abuse in the future. In order to approach this problem, the normative legal research method is used. The data is collected through library research and analyzed qualitatively. The study concludes that several flaws in Indonesian bankruptcy law related to the good faith principle, such as excessively modest bankruptcy petition requirements, lack of governmental supervision in the bankruptcy process, and severe punishment for the bankruptcy fraudsters. In the future, the Indonesian bankruptcy regime is expected to implement an insolvency test, improve the role of the Property and Heritage Agency, and strictly punish bankruptcy fraudsters for minimalizing bankruptcy abuse by bad faith parties.